Non-specific aortic arteritis (Takayasu's disease) : the Cape Town experience - Currer, Trevor H (Department of Surgery, 2017)
Non-specific aortic arteritis remains a disease of unknown aetiology, in which the treatment is empiric, the indications for surgery controversial and the prognosis unpredictable. Most series emanate from the Far East, with few contributions from Africa. The pattern of disease as seen in-Cape Town has not been documented since the study of Schrire and Asherson in 1964, containing 18 cases. In this study at Groote Schuur and Red Cross Children's Hospital from 1952 to 1987, only patients who had been extensively investigated and subjected to angiography were included. strict· inclusion criteria excluded patients with specific forms of aortic arteritis. 220 patients were studied of which 77% were female. Mean age 25(1-66). 68% were "Coloured" or Asian, 24% Black and 8% White. Involvement of the entire aorta was seen in 62%. The· aortic arch was involved in 70% but isolated arch disease occurred in only 9%. Aortic bifurcation disease occurred in 30%, an unusually high incidence. 93% had occlusive disease. 50% had aneurysms, which usually occurred together with occlusive disease. 7 patients presented with ruptured aneurysm. Hypertension due to renal artery stenosis or to coarctation was the commonest presentation (76%). 103 (47%) patients had cardiac disease (hypertensive cardiac failure or aortic incompetence.) Upper or lower limb claudication was present in 77 patients with gangrene in only 11. 43 patients had clinical evidence of cerebrovascular disease. 54 patients are known to have died, with cardiac failure responsible for almost 50%. Follow-up of 5-20 years was possible in 40% of patients. Two-thirds showed no further progression in this period. Vascular reconstruction was performed in 43 patients (21%). Other treatment modalities included corticosteroids (11%) and antituberculous therapy (28%). Proven tuberculosis was present in only 20% of cases. The pattern of disease in Cape Town tends to be diffuse, usually with extensive branch vessel involvement, and thus seldom amenable to reconstructive vascular surgery. Hypertension and cardiac failure are the commonest presenting symptoms and the most frequent cause of death. The aetiology of this condition remains obscure and the pathogenetic link with Tuberculosis is controversial. A significant number of patients have "burnt out" disease, and prolonged survival has been observed.